Evaluasi Terapi Pada Pasien Gastroenteritis Dengan Abdomen Akut - Lamalani, Alia Nur; Abdulkadir, Widy Susanti; Yusuf, Annisa Humaira; Hippy, Fajria Indah; Monoarfa, Magfira Susilowati; Anasiru, Rayhan Firman; Lakoro, Siti Ruqaiyah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Gastroenteritis is one of the major health problems that is still often found in developing countries, especially in vulnerable groups. This study aims to evaluate pharmacological and non-pharmacological therapy in a 43-year-old female patient diagnosed with gastroenteritis due to infection and accompanied by acute abdomen. This study used a case study approach with the SOAP method, based on medical record data at Tombulilato Hospital, Gorontalo. Initial therapy included rehydration using Ringer Lactate, and administration of Omeprazole, Ondansetron, and Ceftriaxone. Therapy was continued with symptomatic drugs such as Paracetamol, Ketoprofen, and Sucralfate. Daily evaluation showed significant clinical improvement, and the patient was discharged on the fourth day in stable condition after therapy was switched to oral form. This study shows the importance of choosing the right therapy, monitoring patient conditions, and patient education in accelerating recovery. It is recommended to replace Omeprazole with Esomeprazole and Ketoprofen with a combination of Paracetamol-Tramadol to reduce the risk of gastrointestinal side effects.